Electrognathographic evaluations of rehabilitated edentulous patients Avaliações eletrognatográficas em pacientes edêntulos reabilitados - Henrique Casselli; Alexandre Brait Landulpho; Wilkens Aurélio Buarque e Silva; Frederico Andrade e Silva (Brazilian Oral Research, 2007)
This study investigated, through computerized electrognathographic evaluations (K6-I Diagnostic System, Myotronics-Noromed Inc., Tukwila, USA), the mandibular movement pattern of 16 patients rehabilitated with complete dentures presenting no symptoms of stomatognathic functional alterations. The patients were instructed to wear an intra-oral appliance for occlusal plane coverage over their usual superior denture and were then rehabilitated with new dentures preserving a free-way space of 3 mm. After sixty days, the occlusal vertical dimension was increased and the modified inferior dentures were used for another 60 days. The obtained results were submitted to the Tukey Test and to the Friedman test, depending on which variable was under consideration, both at a significance level of 5%. The data revealed a significant decrease in free-way space when the first and the last evaluations were compared. No significant differences were found during opening and closing. It was concluded that the presence of a free-way space at the end of the treatment confirms the importance of its existence for maintaining the balance of the masticatory system, assuming the occurrence of a postural repositioning. O objetivo deste estudo foi avaliar por meio de eletrognatografia computadorizada (K6-I Diagnostic System, Myotronics-Noromed Inc., Tukwila, EUA) o padrão dos movimentos mandibulares de 16 pacientes reabilitados com dentaduras completas, livres de alterações funcionais do sistema estomatognático. Os pacientes foram instruídos a utilizar um aparelho intra-oral de cobertura oclusal plana adaptado na prótese usual superior e então reabilitados com novas próteses preservando a existência de um espaço funcional livre de 3 mm. Após 60 dias promoveu-se um aumento da dimensão vertical de oclusão e as próteses inferiores assim modificadas foram utilizadas por mais 60 dias. Os resultados foram submetidos ao Teste de Tukey e ao Teste de Friedman, dependendo da variável em estudo, ambos com 5% de significância. Constatou-se decréscimo significante do espaço funcional livre quando compararam-se a primeira e a última avaliações. Não foram encontradas diferenças durante abertura e fechamento. Concluiu-se que a presença de um espaço funcional livre ao final do tratamento vem comprovar a importância de sua existência na manutenção do equilíbrio do sistema mastigatório, admitindo-se que ocorre o reposicionamento postural.